Report of judgments, advisory opinions and other decisions of the African Court on Human and Peoples' Rights: African Court Law Report Volume 3 (2019) (Pretoria University Law Press (PULP), 2021)
This is the third volume of the Report of judgments, orders and advisory opinions of the African Court on Human and Peoples' Rights. This volume covers decisions from 2018 to 2019. The volume includes all the Judgments, including Separate and Dissenting Opinions, Advisory Opinions, Rulings, Decisions,Procedural Orders and Orders for Provisional Measures adopted by the Court during the period under review. Each case has a headnote setting out a brief summary of the case followed by keywords indicating the paragraphs of the case in which the Court discusses the issue. A subject index at the start of the reports indicates which cases discuss a particular issue. This index is divided into sections on general principles and procedure, and substantive issues.